1979
DOI: 10.1021/j100478a026
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric determination of the dissociation energy of technetium carbide(g)

Abstract: The TcC(g) molecule is observed above a liquid technetium carbide phase of unknown composition by using Knudsen effusion mass spectrometry. Intensity data for Tc(g) between 2229 and 2560 K and for TcC(g) between 2393 and 2595 K give a third-law bond energy of D°0 = (134 ± 7) kcal moT1 for TcC(g). A value of D°0 = (140 ± 2) kcal moT1 is obtained by the second-law method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Diatomic 98 TcC is the only carbide molecule of technetium for which a molecular property has been experimentally measured. 4 For this reason, we have chosen to investigate some of the diatomic spin states, in order to assess the performance of the density functional implementation. Diatomic binding energies can also be used to evaluate 98 TcC 2 carbon atom extraction enthalpies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Diatomic 98 TcC is the only carbide molecule of technetium for which a molecular property has been experimentally measured. 4 For this reason, we have chosen to investigate some of the diatomic spin states, in order to assess the performance of the density functional implementation. Diatomic binding energies can also be used to evaluate 98 TcC 2 carbon atom extraction enthalpies.…”
Section: Resultsmentioning
confidence: 99%
“…The dissociation energy of TcC has been determined experimentally, using electron ionization-Knudsen effusion mass spectrometry, to be 6.02 ( 0.1 eV. 4 Numerous approximations were used in the evaluation of the experimental dissociation energy, including the estimation of (H°2 450 -H°0) ) 0.89 eV, the Gibbs free energy functions for C (s) ,Tc (g) and the estimation of appearance energies for Tc + and TcC + ((0.2 eV, (0.5 eV, respectively). Furthermore, the "equilibrium" assumption does not take into account fragmentations of higher carbides that lead to the formation of TcC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was reported that the development of potential Tc-rich nitride forms with high chemical stability and corrosion resistance [7]. In addition, Tc carbides appear to have especially surprising importance in the fields of nuclear waste management and nuclear medicine [8,9]. Therefore, there is great interest for physicists in experimental [8][9][10][11][12] and theoretical investigations [13,14,25] of technetium carbides.…”
mentioning
confidence: 99%